1989
DOI: 10.1038/340385a0
|View full text |Cite
|
Sign up to set email alerts
|

Motion-deblurring in human vision

Abstract: SUMMARYUnder normal viewing conditions we are little conscious of blur in moving objects, despite the persistence of vision. Moving objects look more blurred in brief than in long exposures, suggesting an active mechanism for suppressing motion blur. To see whether blur suppression would improve visual discrimination of objects, we measured blur discrimination thresholds for moving Gaussian-blurred edges and bars. The observer's task was to decide which of two moving stimuli, presented successively, was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Thus. the findings of Morgan and Benton (1989) for spatialinterval discrimination of two line segments and our present observations appear to be related to the same underlying mechanisms. Stimulus velocity affects discrimination of line separation or grating spatial frequency when the critical information is contained in the medium-high spatial frequency range and has little effect when this information is stored in the low spatial frequency range.…”
Section: Eflect Of Grating Orientation On Spatial-frequency Discriminsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus. the findings of Morgan and Benton (1989) for spatialinterval discrimination of two line segments and our present observations appear to be related to the same underlying mechanisms. Stimulus velocity affects discrimination of line separation or grating spatial frequency when the critical information is contained in the medium-high spatial frequency range and has little effect when this information is stored in the low spatial frequency range.…”
Section: Eflect Of Grating Orientation On Spatial-frequency Discriminsupporting
confidence: 88%
“…McKee (1975, 1977) have For the vernier targets, Westheimer and shown that discrimination thresholds for the McKee (1975) restricted their observations to offset of two vertically oriented lines remains stimulus velocities of 3.5 degjsec and less. In a unaffected by image motion for a range of recent report, Morgan and Benton (1989) replivelocities between 0.5 and 3.5 deg/sec. Intercated the findings of Westheimer and McKee estingly, vernier-resolution thresholds were and expanded their observations to stimulus affected by oblique motion, when the vertical velocities up to 6 degjsec.…”
Section: Eflect Of Grating Orientation On Spatial-frequency Discriminmentioning
confidence: 98%
See 1 more Smart Citation
“…As a reference, the spatial acuity of marmoset reaches 30 cycles/degree (Ordy and Samorajski 1968), suggesting that although activity in area MT is unlikely to match the maximal acuity of activity in retina and area V1, it can provide a spatial representation with behaviorally relevant acuity. Yet, our estimates of spatial precision are difficult to relate to extant measurements of behavioral acuity, which can use form and motion signals, as well as positional signals (Morgan and Benton 1989;Verdon-Roe et al 2006;Westheimer 1987), and are likely to be task dependent.…”
Section: Discussionmentioning
confidence: 97%
“…In principle, these mechanisms restore positional acuity by taking into account the temporal delay at which different photoreceptors have been stimulated. The second approach 7 ' 8 does not invoke a general motiondeblurring mechanism. It assumes that image motion does introduce spatial blur.…”
Section: Introductionmentioning
confidence: 99%